FAKTOR PRESDISPOSING KETERLAMBATAN PERKEMBANGAN PADA ANAK DENGAN CEREBRAL PALSY DI RSJD Dr. RM. SOEDJARWADI PROVINSI JAWA TENGAH - Intan Nugraheni; Lailatif Nadiah Safitri (Universitas Duta Bangsa Surakarta, 2015)
Background: The preliminary study in Region Psychological Hospital Dr. RM. Soedjarwadi Central Java Province obtained approximately 50 patients with cerebral palsy who came to perform stimulation treatments. The report of data result in the Medical Records Installation stated that, cerebral palsy is the first rank diagnosis in the top 10 of the most diagnostic in the Growth Child and Adolescent Clinic of Region Psychological Hospital Dr. RM. Soedjarwadi Central Java Province.Objective: To determine the description of the presdisposing factors the developmental delay in cerebral palsy’s children.Method: The research is descriptive retrospective. The sampling technique used is incidental sampling. Members ofthe sampleamounted to 45respondents. The data analysis technique used is the frequency distribution of descriptive statistics.Result: Most respondents were age 0-5 years (68,89%), male sex (55,56%), had a history of birth cephalic presentation (93.33%), never exposed to toxins / chemicals during the prenatal period (73.33%), were never infected with TORCH during the prenatal period (91.11%), was never infected with an STD during the prenatal period (100%), plan and get excited over the pregnancy (75.56%), spontaneous delivery method (75.56%), were born at term (86.67%), and asphyxia at birth (28.89%).Conclusion: The internal and external factors can affect the developmental delay in cerebral palsy’s children. Keywords: Developmental Delayed, Cerebral Palsy